A Cross-cultural Study of Foshan Paper-cut Art - Li Zhou (Journal of Advanced Research in Education, 2024)
Foshan paper-cut boasts a wide variety of styles, extensive subject matters, and rich cultural connotations. During the process of “Chinese culture going global”, the translation of Foshan paper-cut holds significant historical importance. Nevertheless, the translation of Foshan paper-cut has not received adequate attention. There exist certain issues in the translation of Foshan paper-cut culture, such as the deficiency of cultural elements, generalization of the translated content, and ineffective translation methods, etc. This requires translators to select the most appropriate translation approach based on the different paper-cut corpus and adhere to the translation principles of effect-first and centering on the target audience. Additionally, we can also establish a parallel corpus and a network database to promote Foshan paper-cut art in multiple ways and facilitate cross-cultural exchanges.